Isolation and Identification of Polioviruses from Stool Specimens of Suspected Cases - Inaam Qadir J. Hashmi , Zahid Masood , Khalid Mehmood , Humayun Asghar Muhammed Tayyab ,Abdul Sattar (Journal of Rawalpindi Medical College, 2014)
Background: To study the isolation and identification of polioviruses from the stool specimen of suspected cases of poliomyelitis (polio). Methods : In this descriptive study two poliovirus-sensitive cell lines of human origin HEp-2, and RD were used for poliovirus isolation. Two hundred and two samples of stool specimen were processed according to the WHO recommendations. Supernatant of stool specimen were inoculated on HEp-2, and RD for poliovirus culture, and incubated at 36oC. Cultures were initially set up in growth medium supplemented with serum. After the formation of a confluent monolayer from the cells, cultures were changed to maintenance medium, designed to maintain cultures in healthy state without stimulating growth. The tubes were incubated , and put in racks at inclined angle of 5o , with line (blue for HEp-2, and black for RD cell line) of tube in upper position. Cultures were daily examined for color change from pinkish to yellow, and for appearance of cytopathic effects (CPEs) under the inverted microscope for 10-14 days before discarding as negative. The yellowish coloration indicated the absence of poliovirus while no color change was indicative of presence of poliovirus, and presence of characteristic CPEs production of poliovirus i.e. rounding of cells, and detachment of cells from culture tubes. Tubes showing CPEs were stored at -20oC. Identification of poliovirus isolates was done by mixing the diluted isolates samples, with equal volumes of a set of antisera of known poliovirus serotypes. The antiserum/ poliovirus mixture was incubated for 2 hr to allow binding of antibodies to poliovirus. Afterwards the mixtures were inoculated into cell culture tubes, and examined daily for CPEs. Prevention of the development of CPEs by the specific antiserum, indicated the identity of the poliovirus serotype. The identification of both isolates from RD as well as Hep-2 cell cultures, was carried on as poliovirus susceptibility of these two lines varies. Results: Majority of cases(38.1%) were of 3-12 months, followed by 13-24 months (34.6%). Male to female ratio was 1.4:1.0. Among the suspected cases, 94% were vaccinated, while about 2% were partially vaccinated. Poliovirus was isolated from 28.2% stool specimens of suspected cases of polio. The poliovirus type 1 was found 75.4%, one of the most common among positive cases. 35% cases were found from Punjab and 28% from KPK Conclusion: Most prevalent type of poliovirus is type-1, and the maximum number of polio is found in the province Punjab. The most vulnerable age group for polio was 3-12 months, and the target age less than 5 years, that covered the percentage of total number of cases upto 99%. Moreover, 94.06% cases of polio were unvaccinated.